The GP and the veteran: the Royal College of General Practitioners' veteran-friendly programme. Issue 10 (2nd October 2022) - Simpson, Robin G
Abstract : Retired brigadier Professor Robin G Simpson, veterans' champion at the Royal College of General Practitioners, discusses the veteran-friendly GP practice accreditation programme, and how it can improve care for veterans.